INVESTIGATION OF BALLISTIC PERFORMANCE OF LAMINATED HYBRID COMPOSITES - Yanen, C.; Solmaz, M. Y. (Acad Sci Czech Republic, Inst Thermomechanics, 2016)
In this study, the usability of layered hybrid composite as personal armor material has been investigated experimentally. In the scope of study, 4 hybrid composite materials with different thicknesses and number of layers, have been produced by using fabric with two different weaving type as plain and twill. Then, ballistic tests have been performed and the test results have been investigated. First, 2 test samples with [Glass(10)/Aramid(10)/Carbon(10)] lineup and 30 layers have been produced, the ballistic tests have been performed and the results have been investigated. After observing the success of these two test samples, other two test samples have been produced by reducing the number of layers to 21 with [Glass(10)/Aramid(10)/Carbon(10)] lineup. The ballistic tests have been conducted by using Beretta and 9 mm FMJ bullet according with the international standards (NIJ 0101-06). In the ballistic tests, the speed of bullets and the depth of penetration (DOP) accuring on the test samples have been measured and the damages have been assessed.
22nd International Conference on Engineering Mechanics -- MAY 09-12, 2016 -- Svratka, CZECH REPUBLIC
Keywords: Hybrid composite; Ballistic performance; Armor material